DETERMINING GEOGRAPHICAL INEQUALITIES OF INFORMATION ACCESSIBILITY AND USAGE: THE CASE OF HUNGARY - JAKOBI, Ákos (European Journal of Geography, 2014)
In the era of information and communication technologies it is necessary to clarify what motives are in the background of geographical disparities. The paper firstly sets up a theoretical framework that depending on the phase of technological innovation adaptation, main features of inequalities have different basic characteristics. By the multivariable analysis of information accessibility differences in the Hungarian microregions, basically the physical infrastructural constraints of the information society and economy are determined. Secondly, since an increasing number of people have become able to access the new information channels by today, the factor of accessibility could now be treated as a secondary problem. In contrast with accessibility differences the inequalities of usage come into the forefront of the analyses. Finally, the last section reveals that instead of usage volume differences the inequalities in the quality of information usage should be taken into consideration, when dealing with the newest geographical inequalities of the information age.